One hundred lava flows of Mt. Etna, Italy: July 2019–December 2023 update - Cristina Proietti; Emanuela De Beni; Massimo Cantarero (Journal of Maps)
Integration of multi-sensor, multi-platform remotely sensed data is an effective methodology for monitoring active volcanoes as it ensures a constant data flow, which is needed for repeated eruptive events in brief intervals. It allows broad observation of the eruptive scenario and quantification of the erupted products. We integrated remote sensing data, through GIS software, to map the lava flows of Etna, one of the most active volcanoes in the world. Between July 2019 and December 2023, Etna gave rise to seventy-five eruptive events, mainly from the summit craters, emplacing one hundred lava flows. We updated Etna's 1999-2019 map, with the most recent eruptive products, mapping ninety-three lava flows out of the one hundred-five. For cartographic simplicity, summit flows are grouped by year or eruptive cycle, while flank flows are distinguished by date. To better display the products and highlight the mapping process, we added twenty-one detailed maps to the main map.